Laser beam propagation in nonlinear optical media - Guha, Shekhar, author; Gonzalez, Leonel Pastor, 1971-, author (Boca Raton, F.L. : CRC Press, 2014)
"This book collects the formalisms and equations for calculating laser beam propagation through linear and nonlinear optical media. It provides formulas for simple beam propagation, examines the distribution of electric field amplitudes at various locations in an optical train, includes expressions for nonlinear frequency conversion with arbitrary focusing of beams, and covers linear and nonlinear absorption and thermal refraction. The book compares various calculation methods and offers MATLABʼ programs to numerically evaluate the problems"--provided by publisher